Pengaruh Stres Kerja Terhadap Kinerja Karyawan Pada Kantor Pengelola IT Center Manado - Massie, Rachel N.; Areros, William A.; Rumawas, Wehelmina (Sam Ratulangi University, 2018)
The effort to increase the working of employees is through paying attention to the stress of working. Stress can happen to every individualy human every time because stress is also a part of human life which can not be avoided. People often experience stress if they can not adapt their will with the fact either from inside or from outside of their self. This research means to know how much is the effect of the working stress to the working of employees at the Kantor Pengelola IT Center Manado. This research used quantitative methode and simple regression, using questionair and observation as s technique to get data and the total of the examples in this research are 32 worker. The counting in this research, the researcher used SPSS software version 21 which can show the corelation between the two variable,and how much the effect of such the working stress to the working of worker. The result of this research show that working stress to the working of employees show negative effect, because the mark of coefisien regression is negative that is 0,34. This negative effect means the working stress is getting less so it. influences the increase of working of employees. Bassed on the result analyses data which was managed, it can be concluded that the effect of working stress to the working of employees is on the stage of. Enough corelation that is 0,152, in rate means the effect of working stress to the working employees is 15,2% while the 84,8% are influenced by other variable that was not researched.